Strategi Badan Penanggulangan Bencana Daerah Mengurangi Resiko Bencana Kebakaran di Wilayah Kabupaten Nias - Eka Septianti Laoli; Zebua, Okniel; Harefa, Peringatan (MAMEN: Jurnal Manajemen, 2022)
The purpose of this study is to determine the strategy of the Regional Disaster Management Agency of Nias Regency in reducing the risk of fire disasters in the Nias Regency area. The research method used is descriptive qualitative. The data sources used are primary data sources and secondary data with 7 informants. Data collection techniques using interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the research carried out show that several indicators are used as benchmarks for achieving performance or efforts from BPBDs, including organizational strategies that have an impact on encouraging change to the community directly which are influenced by the values ​​of organizational or agency activities, program strategies to form programs by involving several stakeholders and pay attention to three aspects, namely prevention, mitigation, and preparedness, resource strategy to conduct training and technical guidance in improving the ability of the apparatus, and to provide facilities that can be used by the community. The supporting factors for this activity consist of two factors, namely the first factor is raising united human resources to help the government to reduce the risk of fire disasters through the community/volunteer team and collaboration between agencies, secondly through the application of information systems that use technology tools to provide data and information about disasters in a comprehensive manner. fire special. The inhibiting factor of this activity consists of two factors, namely the first factor is climatic conditions with high heat which make the risk of fire higher. The second factor is human behavior and carelessness in illegally clearing land which can lead to forest fires.